SAT0231 Safety of subcutaneous belimumab in patients with systemic lupus erythematosus: a 6-month open-label extension study. (15th June 2017) - Doria, A; Stohl, W; Schwarting, A; Scheinberg, M; Hammer, A; Kleoudis, C; Groark, J; Fox, NL; Roth, D; Bass, D; Gordon, D
Abstract : Background: Intravenous belimumab (BEL) 10 mg/kg is approved in adult patients with active, autoantibody-positive systemic lupus erythematosus (SLE), on standard SLE therapy (SoC). A Phase III, double-blind (DB), study of subcutaneous (SC) BEL 200 mg weekly plus SoC showed efficacy and safety in patients with SLE. Objectives: The ongoing safety and efficacy of BEL 200 mg SC weekly were assessed in a 6-month open-label extension (OLE) study. Methods: Patients with SLE who completed BLISS-SC (BEL112341; NCT01484496 ), a Phase III, randomised (2:1), DB, placebo (PBO)-controlled, 52-week trial of BEL 200 mg SC, were eligible to enter a 6-month OLE; the outcomes are reported here. Patients were maintained on weekly BEL (BEL group) or switched from PBO to BEL (PBO to BEL group). Baseline differed according to study treatment (Day 0 of the DB phase for BEL; Week 52 of the DB phase for PBO to BEL). The primary focus was safety, evaluated by adverse event (AE) reporting, laboratory tests and immunogenicity. OLE AEs were those occurring on or after the first OL dose. Efficacy evaluations were conducted, at reduced frequency, as per the DB phase 1 . Results: Overall, 677 patients completed the DB phase, 662 entered the OLE; 625 completed. Mean baseline Safety of Estrogens in Lupus Erythematosus National Assessment-Systemic Lupus Erythematosus Disease Activity Index scores were 10.4 (BEL group) and 5.8 (PBO to BEL group, implying better SoC in the DB phase); Systemic Lupus International Collaborating Clinics/ACR Damage Index scores were similar (0.7 and 0.6, respectively). Most OLE AEs were mild/moderate in severity. Despite differences in BEL exposure (BEL: 1 year [DB]; 6-month OLE, and PBO to BEL: 6-month OLE), OLE AE rates were similar (table). Infections and infestations were the most frequent AEs (190/662, 28.7%; drug-related, 55/662, 8.3%; serious AEs [SAEs]; 17/662, 2.6%). AEs of depression/suicide/self-injury (12/662, 1.8%), infections of special interest (17/662, 2.6%), post-injection systemic reactions (21/662, 3.2%) and local injection site reactions (4/662, 0.6%), were low. Two deaths occurred (metabolic acidosis; pneumonia and acute respiratory failure); unrelated to study drug. The percentage of patients worsening (≥2 grade) from baseline was low for all clinical laboratory parameters. Three patients had anti-BEL immune responses during the OLE or follow-up; this resolved on subsequent testing. Efficacy was maintained across the OLE. Conclusions: No new differences in safety and efficacy of BEL 200 mg SC plus SoC were seen in this 6-month OLE study compared with the DB phase. References: Stohl W et al. Arthritis Rheumatol 2017;doi:10.1002/art.40049. Acknowledgements: Study funded by GSK. Sam Halliwell, PhD, Fishawack Indicia Ltd, UK, provided editorial assistance funded by GSK. Disclosure of Interest: A. Doria Speakers bureau: GSK, Pfizer, AstraZeneca, Celgene, Eli Lilly, Baxalta, W. Stohl Grant/research support from: GSK, Celgene, Janssen Research & Development, Pfizer and Sanofi-Aventis Pharmaceutical, Consultant for: GSK, Celgene, Janssen Research & Development, Pfizer and Sanofi-Aventis Pharmaceutical, A. Schwarting Consultant for: GSK, M. Scheinberg Consultant for: Pfizer, GSK, Epirus, Samsung Bioepis, Janssen Pharmaceutica Products, L.P., A. Hammer Shareholder of: GSK, Employee of: GSK, C. Kleoudis Shareholder of: GSK, Employee of: Parexel, J. Groark Shareholder of: GSK, Employee of: GSK, N. L. Fox Employee of: GSK (former employee), D. Roth Shareholder of: GSK, Employee of: GSK, D. Bass Shareholder of: GSK, Employee of: GSK, D. Gordon Shareholder of: GSK, Employee of: GSK